Teachers’ Perception towards Online Science Learning during the Pandemic - Sajidan Sajidan; Fadhil Purnama Adi; Idam Ragil Widianto Atmojo; Moh Salimi; Roy Ardiansyah; Adelia Anisa (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to describe the perceptions of SD Angkasa Colomadu teachers on online science learning during the pandemic. This research used descriptive qualitative research methods and a case study approach. The subjects of this study were three teachers of grades IV, V, and VI SD Angkasa Colomadu in the academic year 2020/2021. Data collection techniques used interviews and documentation. The data validity test techniques used the triangulation technique. Data analysis techniques used interactive analysis techniques Miles and Huberman consisting of data reduction, data display, and conclusions. The results show that the teachers felt that learning sciences in the network was not optimal. Teachers do not optimally apply basic process skills. The teachers feel the limitation in the communication process.  They also have a restriction on directing the students to formulate hypotheses, conclude the material, guide experimental activities, attract students to ask questions, guide the measurement process, guide observation activities, classify, interpret, and predict processes due to media limitations. On the other hand, teachers feel that online learning makes teachers more innovative, creative, and able to take advantage of cellphones, computers, and the internet in learning activities, especially in learning science online during the pandemic period.